Selection of surgical approach and role of lymph node dissection at colorectal cancer - P. V. Melnikov; S. V. Savenkov (Тазовая хирургия и онкология, 2015)
Historically, colorectal surgeons extended lymph nodes dissection level. However, it is still controversial issues: what is considered to be an extended lymph node dissection, why and to whom it is better to do it, etc. Moreover, the prognostic value of extended lymph dissection was demonstrated in trials with a low level of evidence and has different degrees of recommendation in different countries and regions. On one hand positive apical lymph nodes in colon cancer achieves 17 % and its risk increasing with tumor penetration into bowel wall, and it is an independent negative prognostic factor with 5 years overall surveillance less 45 %. An indirect data (increased the number of lymph nodes, integrity of removed mesocolon, lymphovascular length, etc.) showed better outcomes with extended lymph node dissection. More controversy is extended lymph node dissection for rectal cancer, the current standard of treatment which is at chemoradiotherapy and/or total mesorectumectomy for T3–4N0–2. Because there is no evidence that lateral pelvic node dissection in rectal cancer improves disease-free survival and overall survival, as well as high ligation of the inferior mesenteric artery. And the presence of pelvic and inferior mesenteric lymph node metastases, identifying average in 7 %, is associated with a high level of local recurrences till 44 % and low survival rate not more 42 % in 5 years. The answer to this question may be conducting multicenter randomized trials.